Indexing and abstracting in theory and practice - Lancaster, Frederick Wilfrid (Champaign University of Illinois, Graduate School of Library and Information Science, 1998)
Award-winning author F.W. Lancaster has revised his widely used text, Indexing and Abstracting in Theory and Practice, to address growing complexities in the field. New chapters in the second edition feature multimedia sources and indexing within the Internet; chapters on text searching, automatic processing methods, and the future of indexing and abstracting are substantially revised. The first nine chapters, covering basic principles and theories, are updated and the section of practical exercises is modified by use of the current edition of UNBIS Thesaurus Researchers from a wide range of disciplines are now involved in content analysis activities that formerly were the sole concern of members of the library and information science field. At the same time, indexing and abstracting have grown in interest within other major disciplines, such as medicine. As a result, relevant articles have become increasingly scattered throughout varied literatures, and a wide range of technologies such as linguistics, computer science, artificial intelligence, and pattern recognition now impinge upon the subject matter of this book, providing the impetus for updating a text noted for both its practicality and attention to theoretical underpinnings. As with the first edition, Indexing and Abstracting in Theory and Practice remains primarily a text for teaching the subject. However, it also holds value for managers of information services and others concerned with indexing, abstracting, and all related issues of content analysis. Chapters focus on indexing principles, indexing practice, consistency and quality of indexing, the types and functions of abstracts, writing and evaluating the abstract, enhancing indexing, natural language in information retrieval, automated indexing and abstracting, indexing of multimedia sources, indexing within the Internet, and the future of indexing and abstracting services. The section of exercises provides concrete illustrations of the text's major points.--Provided by publisher.
Includes bibliographical references (p. 366-397) and index.
Keywords: Abstracting; Indexing